Development of Android Chemistry Comics as an Independent Learning Application to Improve Student Learning Outcomes - Sri Adelila Sari*; Melysa Tioro Exaudie Lubis (Universitas Syiah Kuala, 2021)
Teachers often use printed book media in learning. Rarely do they want to develop and vary learning media with the aim of making the learning process more interesting. As a result, the lack of student interest in learning results in low student learning outcomes. This study was aimed to develop android chemistry comics (chemondro) on the material for the reaction rate of class XI IPA SMA N 1 Garoga. The method used is the ADDIE R D model, namely analysis, design, development, implementation, and evaluation. The analysis stage was carried out by analyzing the needs in the form of student characteristics and identifying learning media. The design stage included flowchart design and chemondro. The design results were then developed, then the application was given to the validator for a feasibility test. The implementation stage was carried out in class XI SMA N 1 Garoga. Furthermore, student learning outcomes were measured at the evaluation stage using tests. The results of this study found that chemondro-based chemical comics could be developed with the 3.6 eligibility criteria very well. The learning outcomes were found to be 81.91 in the experimental class compared to 71.76 in the control class. This study concluded that chemondro-were very suitable for use in chemistry learning, especially on the material of reaction rates and student learning outcomes were achieved with good criteria.